Exosymbiotic microbes within fermented pollen provisions are as important for the development of solitary bees as the pollen itself. Issue 4 (6th April 2022) - Dharampal, Prarthana S.; Danforth, Bryan N.; Steffan, Shawn A.
Abstract: Developing bees derive significant benefits from the microbes present within their guts and fermenting pollen provisions. External microbial symbionts (exosymbionts) associated with larval diets may be particularly important for solitary bees that suffer reduced fitness when denied microbe‐colonized pollen. To investigate whether this phenomenon is generalizable across foraging strategy, we examined the effects of exosymbiont presence/absence across two solitary bee species, a pollen specialist and generalist. Larvae from each species were reared on either microbe‐rich natural or microbe‐deficient sterilized pollen provisions allocated by a female forager belonging to their own species (conspecific‐sourced pollen) or that of another species (heterospecific‐sourced pollen). Our results reveal that the presence of pollen‐associated microbes was critical for the survival of both the generalist and specialist larvae, regardless of whether the pollen was sourced from a conspecific or heterospecific forager. Given the positive effects of exosymbiotic microbes for larval fitness, we then examined if the magnitude of this benefit varied based on whether the microbes were provisioned by a conspecific forager (the mother bee) or a heterospecific forager. In this second study, generalist larvae were reared only on microbe‐rich pollen provisions, but importantly, the sources (conspecific versus heterospecific) of the microbes and pollen were experimentally manipulated. Bee fitness metrics indicated that microbial and pollen sourcing both had significant impacts on larval performance, and the effect sizes of each were similar. Moreover, the effects of conspecific‐sourced microbes and conspecific‐sourced pollen were strongly positive, while that of heterospecific‐sourced microbes and heterospecific‐sourced pollen, strongly negative. Our findings imply that not only is the presence of exosymbionts critical for both specialist and generalist solitary bees, but more notably, that the composition of the specific microbial community within larval pollen provisions may be as critical for bee development as the composition of the pollen itself. Abstract : We report that exosymbiotic microbes within larval pollen provisions are critical for the development of solitary bees, regardless of their foraging strategy. Furthermore, the particular microbial community composition within pollen provisions is as critical as the pollen source itself, both factors being significant and co‐equal drivers of bee fitness.